6(x+3)-75=5(x-10)

Simple and best practice solution for 6(x+3)-75=5(x-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+3)-75=5(x-10) equation:


Simplifying
6(x + 3) + -75 = 5(x + -10)

Reorder the terms:
6(3 + x) + -75 = 5(x + -10)
(3 * 6 + x * 6) + -75 = 5(x + -10)
(18 + 6x) + -75 = 5(x + -10)

Reorder the terms:
18 + -75 + 6x = 5(x + -10)

Combine like terms: 18 + -75 = -57
-57 + 6x = 5(x + -10)

Reorder the terms:
-57 + 6x = 5(-10 + x)
-57 + 6x = (-10 * 5 + x * 5)
-57 + 6x = (-50 + 5x)

Solving
-57 + 6x = -50 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-57 + 6x + -5x = -50 + 5x + -5x

Combine like terms: 6x + -5x = 1x
-57 + 1x = -50 + 5x + -5x

Combine like terms: 5x + -5x = 0
-57 + 1x = -50 + 0
-57 + 1x = -50

Add '57' to each side of the equation.
-57 + 57 + 1x = -50 + 57

Combine like terms: -57 + 57 = 0
0 + 1x = -50 + 57
1x = -50 + 57

Combine like terms: -50 + 57 = 7
1x = 7

Divide each side by '1'.
x = 7

Simplifying
x = 7

See similar equations:

| 5-5x=-8x+14 | | (12-15)3= | | 192=72x^2+24 | | 2x+3(x-4)=(x-3) | | A+BX=CX+D | | 4(Z+7)-6=2 | | 29-(-q)=86 | | xsquared+8x-5=15 | | g-13.37=-23 | | (0.5)(y)=3 | | 5y=175 | | 3(x-1)+60=8(x+4) | | g(-3)=2x-5 | | -30+6x=x | | -19-r=-57 | | y+17.5=49 | | -1+6x+x=-85 | | Q-65=875 | | (4+3x)(2-x)+(4-3x)(2+x)=22 | | 5x-2+4x=43 | | w+-28=-17 | | -38=-x+4x-5 | | 22x=44y | | 17y-12y=25 | | 3x-4-8x+12= | | 15-4X=-X | | 3(x-3)+5=4(x-2)-10 | | 5ab-6ab+a= | | 2senx-cosx=-4 | | P=20+6ln(2q+1) | | 13x+15=3x+215 | | B+280= |

Equations solver categories